Wings of fire - Brown, Dale (Putnam's Sons, 2002)
Former U.S. Air Force general Patrick McClanahan finds himselfin the middle of a war between Libya and Egypt.
Keywords: Adventure fiction; Suspense fiction; Air pilots; Military; Americans; McLanahan; Patrick (Fictitious character)